Innovazione: quale miglioramento? - Micol Rispoli (Ardeth, 2019)
The term innovation is commonly considered synonymous with improvement. This particularly happens in liberal societies, whose economic dynamics are expressed both in the production of objects and in the design of new services. This meaning in fact has emerged in a productive and social context in which high technology is able to produce increasingly sophisticated instruments and devices that, although requiring a very high level of scientific knowledge, are offered for mass consumption. Moreover, most of the users can only partially understand their functioning.Today innovation seems to be a permanent imperative both at the level of companies and industries, and at the level of institutions, that widely use this term when reforming their services. However, even though the term is mostly used to feed the vicious circle of consumerism, it could also refer to shared design processes and practices capable of promoting unprecedented methods of social construction.